Risk factors for pre-clinical atherosclerosis in adolescents with type 1 diabetes. (April 2023) - Morandi, Anita; Piona, Claudia; Corradi, Massimiliano; Marigliano, Marco; Giontella, Alice; Orsi, Silvia; Emiliani, Federica; Tagetti, Angela; Marcon, Denise; Fava, Cristiano; Maffeis, Claudio
Highlights: Traditional risk factors explain only part of the risk of pre-clinical atherosclerosis in type 1 diabetes (T1D). Oxidative stress, oxidized lipoproteins, and glycemic variability may be novel predictors of pre-clinical atherosclerosis. Oxidative stress, male gender, insulin dose, lipids and blood pressure, but not glycemic variability, contributed to the variance of pre-clinical atherosclerosis markers in adolescents with T1D. Abstract: Aims: To assess whether, besides "traditional" risk factors, overall oxidative stress, oxidized lipoproteins, and glycemic variability are associated with early macro-vascular damage in type 1 diabetes (T1D). Methods: In 267 children/adolescents with T1D (130 girls, age 9.1–23.0 years) we evaluated: derivatives of reactive oxygen metabolites [d-ROMs], serum total antioxidant capacity [TAC] and oxidized LDL-cholesterol [oxLDL]; markers of early vascular damage (Lipoprotein-associated phospholipase A2 [Lp-PLA2], z-score of carotid intima-media thickness [z-cIMT] and carotid–femoral pulse wave velocity [z-PWV]); CGM metrics of four weeks preceding the visit, central systolic/diastolic blood pressures (cSBP/cDBP), and HbA1c, z-score of BP (z-SBP/z-DBP) and circulating lipids longitudinally collected since T1D onset.. Three general linear models were built with z-cIMT, z-PWV adjusted for current cDBP, and Lp-PLA2 as independent variables. Results: The z-cIMT was associated with male gender (B = 0.491, η 2 = 0.029, p = 0.005), cSBP (B = 0.023, η 2 = 0.026, p = 0.008) and oxLDL (B = 0.022, η 2 = 0.022, p = 0.014). The z-PWV was associated with diabetes duration (B = 0.054, η 2 = 0.024, p = 0.016), daily insulin dose (B = 0.52, η 2 = 0.018, p = 0.045), longitudinal z-SBP (B = 0.18, η 2 = 0.018, p = 0.045) and dROMs (B = 0.003, η 2 = 0.037, p = 0.004). Lp-PLA2 was associated with age (B = 0.221, η 2 = 0.079, p = 3*10 −6 ), oxLDL (B = 0.081, η 2 = 0.050, p = 2*10 −4 ), longitudinal LDL-cholesterol (B = 0.031, η 2 = 0.043, p = 0.001) and male gender (B = -1.62, η 2 = 0.10, p = 1.3*10 7 ). Conclusions: Oxidative stress, male gender, insulin dose, diabetes duration and longitudinal lipids and blood pressure, contributed to the variance of early vascular damage in young patients with T1D.